Perceptions on interaction design in Malaysia - Hussein, Idayawati; Abu Seman, Esmadi Abu; Mahmud, Murni (Springer-Verlag, 2009)
Even though researchers have introduced Human Computer Interaction (HCI) methodologies, since 1980's, Malaysia's user interface is still considered inadequate. Despite being aware of the importance of usable design, several non-technical issues have more significant influence towards poorly designed user interface in Malaysia. This paper reports the findings of a study of interaction design and/or any HCI methodologies in practice among Malaysian companies for software design and computer-related design development. The research involved senior Information Communication Technology (ICT) managers and focused on the application developers, whose job descriptions and responsibilities vary. The study used semi-structured interviews and a focus group study to uncover the current perceptions of people involved in ICT project development. The findings serve as a pointer to the Malaysian government and stakeholders towards the improvement of user interface design.